Nutritional Status, Physical and Psychomotor Development of Premature Infants: A Prospective Observational Comparative Study - Tatiana V. Turti; Anna A. Gorbacheva; Olga L. Lukoyanova (Union of pediatricians of Russia, 2018)
Background. The development of premature infants is slower than that of term ones, often due to nutritional status disorders in preterm infants. Objective. Our aim was to study the nutritional status, physical, and psychomotor development of infants.Methods. Nutritional status - the composition (the ratio of fat and fat-free tissues) and the value of lean body mass (LBM) - was assessed by plethysmography and densitometry; physical development - by measuring the mass and length of the body, the circumference of the head and chest, calculating the body mass index (BMI); psychomotor development - assessing compliance with the schedule of neuropsychological development of infants (GNOM). The examination was carried out at 12-14 and 16-18 weeks of the corrected age for preterm and actual age for full-term infants. Initially, the diet of infants was assessed by determining the amount, content of macronutrients and energy in the breast milk and/or milk formula and complementary food consumed. The diet was considered to be balanced if the diet parameters diverged not more than 10% of the norm.Results. The study included 23 preterm infants with extremely low (ELBW), 20 - with very low (VLBW), 34 - with low body weight (LBW), and 33 full-term infants. At 12-14 weeks of the corrected age, the magnitude of LBM in infants with ELBW - 3,397 (3,096; 3,608) and with VLBW - 3,824 (3,797; 3,899) was lower than in infants with LBW - 4,497 (4,034; 4,651) and full-term infants - 4,511 (3,887; 4,647) (Kruskal-Wallis test, p = 0.048). Protein balanced diet was in 2 (9%) infants with ELBW, energy balanced diet - in 1 (4%) infant. Among infants with ELBW, 17/23 (74%) referred to the risk group, 6/23 (26%) - to the developmental disorder group. Compared with infants with ELBW and VLBW, infants with LBW and full-term infants had a higher LBM and, correspondingly, higher body weight and BMI. Improvement of the nutritional status after 4-6 weeks due to correction of protein and energy consumption in infants with ELBW was accompanied by some increase in lean body mass, while its proportion was much higher and the proportion of fat mass was lower, which was accompanied by an improvement in the psychomotor development in individual infants: 5/23 (22%) became age-appropriate, and in the risk group of developmental disorders, the proportion of infants decreased from 17 (74%) to 13/23 (57%). The obtained results testify to the influence of nutritional status on the physical and psychomotor development of infants.Conclusion. The importance of dynamic assessment of the nutritional status of premature infants with individualized correction of their diet for improving the physical and psychomotor development of the child during the first year of life is shown.